Transient Pressure Analysis for Multifractured Horizontal Well with the Use of Multilinear Flow Model in Shale Gas Reservoir. (7th February 2020) - Wang, Guangdong; Jia, Ailin; Wei, Yunsheng; Xiao, Cong
Abstract : Shale gas reservoirs (SGR) have been a central supply of carbon hydrogen energy consumption and hence widely produced with the assistance of advanced hydraulic fracturing technologies. On the one hand, due to the inherent ultralow permeability and porosity, there is stress sensitivity in the reservoirs generally. On the other hand, hydraulic fractures and the stimulated reservoir volume (SRV) generated by the massive hydraulic fracturing operation have contrast properties with the original reservoirs. These two phenomena pose huge challenges in SGR transient pressure analysis. Limited works have been done to take the stress sensitivity and spatially varying permeability of the SRV zone into consideration simultaneously. This paper first idealizes the SGR to be four linear composite regions. What is more, the SRV zone is further divided into subsections on the basis of nonuniform distribution of proppant within the SRV zone which easily yields spatially varying permeability away from the main hydraulic fracture. By means of perturbation transformation and Laplace transformation, an analytical multilinear flow model (MLFM) is obtained and validated as a comparison with the previous models. The flow regimes are identified, and the sensitivity analysis of critical parameters is conducted to further understand the transient pressure behaviors. The research results provided by this work are of significance for an effective recovery of SGR resources.